Spiritual and personal orientation of nurses’ practice in dealing with palliative patients - Maryna Pylypivna Tymofiieva; Iryna Vasylivna Marchuk; Oleksandr Tanasiiovych Marchuk (Insight: the psychological dimensions of society, 2022)
The nursing staff holds pride of place in medical communities amidst the modern dimension of the world’s requirements for this profession. In addition to basic professional qualities and competencies, a nurse must have significant spiritual values because it influences the patient’s life and health and the treatment of his soul as an essential component of personality, most importantly not only at the final stages of life caused by disease progression but also in remission. The purpose of the study is to elucidate research findings to determine the motivation for the spiritual development of personality and spiritual values of a palliative care nurse. Methods. To achieve the purpose, theoretical research methods were used: analysis, synthesis, and generalization. Solving research problems involved the methodology for diagnosing thinking direction and predominant personal motives “Bookshelf” (Pomytkin, 2013). The methodology covers the basic qualities of a nurse’s spiritual development, as follows: physiological needs, security and confidence, love for neighbor, appreciation and respect, self-actualization, spiritual self-improvement, service, wisdom, righteousness, and holiness. Nurses working in different fields of medical care, including palliative and hospice, participated in the study. Results. It was found that the vast majority of respondents believe that the main directions of their thinking and ideas about personal development are determined by the level of physiological needs, a sense of security and confidence, love, appreciation, and respect. At the same time, holiness, righteousness and wisdom are insignificant to most respondents. According to the questionnaire, we concluded that nurses need in-depth work to actualize their spiritual development to fully cooperate with palliative patients and create the most favorable environment for their stay in a health care facility, hospice, or home.